Pelatihan Pembuatan Barcode Paket Wisata Grand Watudodol Banyuwangi - Ratna Mustika Yasi; Fathul Hadi, Charis; Fita Lestari, Riska; Arya T Candra; Prasetyo, Andiko (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Banyuwangi Regency is one of the participating districts in order to accelerate local economic growth through the tourism industry. Banyuwangi Regency has a very diverse appeal in the tourism sector. There are natural sights such as beaches, mountains, forests, national parks, culture, and others. Grand Watudodol Beach is a beach that has trip packages for water tourism to Menjangan Island and Tabuhan Island. The tour package is only focused on water travel, but the beach (costal) has not been explored much and the visitors just sit back and do not enjoy the natural resources available at Grand Watudodol. In the digital age, the use of technology as a means of promotion, especially for the world of tourism, has become one of the marketing strategies. One of the uses of this technology is the creation of tour package barcodes at Grand Watudodol. A bar code (or barcode) is a collection of data that can be read by a machine, this barcode works by the system collecting data in widths (lines) and space parallel lines which is referred to as a barcode or linear symbology. Based on the results of community service activities, it was found that the use of barcodes in the medium for conveying information on tour packages can attract buyers, especially the effectiveness in displaying package descriptions to make it easier and more efficient so that tourism business development can compete.